PREVENTION OF INCIDENCE OF DRUG NUTRIENT INTERACTION IN HOSPITALIZED PATIENTS (International Journal of Food and Nutritional Sciences, 2025)
This single-centre, cross-sectional prospective study aims to reduce Drug-Nutrient Interactions (DNI) by educating patients on food-drug interactions and adjusting diets accordingly. Registered Dietitians (RDs) develop tailored dietary guidelines, while the Health Information Management System (HIMS) enables real-time diet adjustments during hospitalization. Clinical Pharmacists and RDs collaborate to provide integrated educational materials at discharge, following CDSCO and ICMR standards. Counseling is delivered efficiently during the hospital stay and upon discharge. The patient-to-staff ratio is 20:1 for RDs and 30:1 for clinical pharmacists. This study underscores the importance of DNI counseling and highlights how automation enhances personalized nutrition management and improves drug and nutrient efficacy.